Fatigue fracture of ductile cast iron crankshaft - Šiđanin, Leposava; Miličev, Slavica; Matović, Nada (Journal of Production Engineering, 1990)
Crankshaft is very important part in automotive industry and can be produced either as forged steel part of as casting from ductile iron. If it is done as a casting part from ductile iron the standard properties are very specific and strong limited. Many tests of material control are included. In this paper detailed investigation of pilot series of crankshafts produced from pearlite nodular iron grade NIXO, were performed. In addition to standard mechanical properties and microstructure of pearlite ductile iron, fatigue life and fatigue limit were deermined. The fatigue tests were carried out on crankshaft segments named series I and II with axial bend loading. For crankshaft series II the bending moment data to estimate fatigue life and fatigue limit, were obtained. However, fatigue life and fatigue limit for crankshaft of series I were not determined. All specimens were failed below 2x10 cycles. The cause of failure is microporosity under the surface of as-cast crankshafts. After machining the micro-porosity developed into the planar defect and reduced drastically fatigue fracture process.